SOCIALIZATION OF SHARIA ECONOMICS AND FINANCE AT SMKN 1 KALOSI ENREKANG - Sirajuddin Sirajuddin; Trisno Wardy Putra; Muhammad Nasri Katman; Idris Parakkasi; Faturrahman Faturrahman; Andi Syathir Sofyan; Muslihati Muslihati (Jurnal Pengabdian Masyarakat Ekonomi dan Bisnis Digital, 2024)
Sharia economic and financial literacy plays a crucial role in shaping the mindset and financial decision-making of the younger generation, especially in Indonesia as a country with a Muslim majority population. However, the level of sharia financial literacy among the younger generation is still relatively low, which can have an impact on their understanding and participation in the sharia-based financial system. This study highlights efforts to improve sharia financial literacy through socialization activities at SMKN 1 Kalosi Enrekang, which involve lectures, interactive discussions, and educational approaches. This program aims to equip students with a comprehensive understanding of sharia financial principles and products, so that they can make financial decisions that are in accordance with Islamic values. In addition, the integration of sharia financial literacy in the education curriculum and the use of digital technology are expected to strengthen sharia financial inclusion and support sharia-based economic growth.